Reflective thinking focuses of intellectual disability students in solving mathematics problems involving the context of traditional ceremonies - Serang, Maeya; Ratumanan, Tanwey Gerson; Matitaputty, Christi; Moma, La (Jurnal Elemen, 2025)
Students’ mathematical reflective thinking skills are not yet fully developed, especially among students with disabilities. To address this issue, culture-based problems can be applied as a learning approach. This study aims to describe students' reflective thinking skills in solving problems related to Maluku cultural contexts, such as traditional events. This research uses a qualitative approach. The subjects were two students with disabilities selected based on specific criteria from a State Junior High School in Maluku Province, Indonesia. The instruments used were two problem-solving tasks and interview guidelines. Data analysis involved data reduction, presentation, and drawing conclusions. The results showed that one student was able to solve the problem well, demonstrating reflective thinking. However, the other student faced difficulties, especially in the reacting stage, where they struggled to understand the given problems, which hindered the overall reflective thinking process. The progress shown by one student indicates that culture-based problems offer positive benefits for students with intellectual disabilities. Therefore, schools are encouraged to integrate Maluku culture-based content into the curriculum and apply strategies that foster reflective thinking.